2016
DOI: 10.1038/modpathol.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Analytic validation of a clinical-grade PTEN immunohistochemistry assay in prostate cancer by comparison with PTEN FISH

Abstract: PTEN loss is a promising prognostic and predictive biomarker in prostate cancer. Because it occurs most commonly via PTEN gene deletion, we developed a clinical-grade, automated and inexpensive immunohistochemical assay to detect PTEN loss. We studied the sensitivity and specificity of PTEN immunohistochemistry relative to 4-color fluorescence in situ hybridization (FISH) for detection of PTEN gene deletion in a multi-institutional cohort of 731 primary prostate tumors. Intact PTEN immunostaining was 91% speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…[8][9][10][11][12] While PTEN loss at the genomic level may be evaluated by different techniques, PTEN immunohistochemistry (IHC) is a simple, yet sensitive and specific approach to detect this underlying genetic abnormality. 7,[15][16][17] The goal of this study, therefore, was to evaluate for correlations between PTEN loss by immunohistochemistry and specific histologic features validated as predictive of an aggressive clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] While PTEN loss at the genomic level may be evaluated by different techniques, PTEN immunohistochemistry (IHC) is a simple, yet sensitive and specific approach to detect this underlying genetic abnormality. 7,[15][16][17] The goal of this study, therefore, was to evaluate for correlations between PTEN loss by immunohistochemistry and specific histologic features validated as predictive of an aggressive clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent studies using diagnostic needle biopsies, it has been proposed that an initial analysis of PTEN expression could be carried out using immunohistochemistry. Thereafter, regions of tumor or suspicious areas in the biopsy that have reduced expression of PTEN protein, or are otherwise indeterminate by immunohistochemistry, could then be analyzed by PTEN FISH as a reflex test [18]. This general approach would be in keeping with the emerging consensus for several types of oncologic pathology tests such as those for breast [19], lung [6,20], and melanomas [21], in which the primary immunohistochemistry analysis can be followed by reflex FISH for cases that are inconclusive.…”
Section: Clinically Significant Gene Losses In Human Cancermentioning
confidence: 99%
“…PTEN deletion associates with poor outcome and is an established prognostic biomarker for prostate cancer. Analysis of prostatic tissue by Immunohistochemistry (IHC) or Fluorescence in situ hybridization (FISH) demonstrated that PTEN loss is associated with prostate cancer biochemical recurrence, disease progression and metastasis [58][59][60][61][62][63].…”
Section: Pten Loss and Erg Rearrangementsmentioning
confidence: 99%